The impact of gender on The efficacy of immune checkpoint inhibitors in cancer patients: The MOUSEION-01 study. (February 2022) - Santoni, Matteo; Rizzo, Alessandro; Mollica, Veronica; Matrana, Marc R.; Rosellini, Matteo; Faloppi, Luca; Marchetti, Andrea; Battelli, Nicola; Massari, Francesco
Graphical abstract: Highlights: Previous studies and meta-analysis have suggested the possible existence of sex-related differences in response to immunotherapy. We conducted a meta-analysis aimed at systematically exploring the presence of sex-related differences in patients treated with ICI. This study is the most updated and comprehensive meta-analysis tackling this important and under-discussed topic. According to our results, slight differences in terms of antitumor efficacy were highlighted between male and female patients. Sex-driven differences in immune checkpoint inhibitors efficacy remain an important and under-discussed aspect. Abstract: The primary endpoint of MOUSEION-01 was to assess overall survival (OS) in male and female patients receiving immune checkpoint inhibitors versus control treatments, calculating the pooled OS Hazard Ratio (HR) and 95 % Confidence Interval (CI) in both groups. 37 randomized phase III studies and 22646 patients (16382 men and 6264 women) were included. In patients treated with immunotherapy (as monotherapy or in combination with other agents), the pooled OS HR was 0.78 (0.75−0.82) and 0.77 (95 % CI, 0.72−0.83) in male and female subjects, respectively. The pooled HR for OS in male patients treated with single-agent immunotherapy versus control was 0.77 (95 % CI, 0.70−0.85), while this benefit was smaller in female patients (HR, 0.81; 95 % CI, 0.73−0.9). Our findings highlight that high-quality trials accounting for potential confounders are needed before being able to suggest a real effect of the patient's gender on immune checkpoint inhibitors efficacy in different settings.